2011
DOI: 10.1093/icvts/ivr030
|View full text |Cite
|
Sign up to set email alerts
|

Web-based versus traditional lecture: are they equally effective as a flexible bronchoscopy teaching method?

Abstract: This study compares the traditional live lecture to a web-based approach in the teaching of bronchoscopy and evaluates the positive and negative aspects of both methods. We developed a web-based bronchoscopy curriculum, which integrates texts, images and animations. It was applied to first-year interns, who were later administered a multiple-choice test. Another group of eight first-year interns received the traditional teaching method and the same test. The two groups were compared using the Student's t-test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In a randomized comparison of training using online curriculum or classroom teaching, it has been shown that both methods are equivalent in improving the cognitive knowledge of trainees in bronchoscopy when measured using a multiple-choice question-based assessment. [367]…”
Section: Training In Flexible Bronchoscopymentioning
confidence: 99%
“…In a randomized comparison of training using online curriculum or classroom teaching, it has been shown that both methods are equivalent in improving the cognitive knowledge of trainees in bronchoscopy when measured using a multiple-choice question-based assessment. [367]…”
Section: Training In Flexible Bronchoscopymentioning
confidence: 99%
“…Studies have shown a difference in comprehension levels of candidates who receive 3D animation teaching v. traditional teaching. [14,15] The design of some of these studies may not explain the impact of the teaching methods too well, as they did not have pre-and post-tests to measure an intervention-attributable impact score. [16] The inclusion of pre-and post-tests in the study design seeks to isolate the existing baseline knowledge before intervention from the acquired new knowledge after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Lecture-based education is one of the methods of face-to-face teaching with a long history widely used nowadays [19]. This is a face-to-face teaching technique with direct relationship between the teacher and the student [23] still used as a cheap and effective method at universities to teach a large number of learners simultaneously. Thus, the interaction between learners and teachers is established to some extent [18,24,25].…”
Section: Introductionmentioning
confidence: 99%